Mitigating DDoS attacks using a resource sharing network - Khan, Farabi Fardin; Hossain, Nafis Mohaimin; Mahmud, Toushif; Anwar, Sad Bin; Islam, Sirajul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.